Development of ciprofloxacin radiopharmaceutical formulation in single vial - Nurlaila Z; Maula Eka S; Eva Maria W (Indonesian Journal of Pharmacy, 2010)
Bacterial infection diseases is the greatest death causes in Indonesia. Detection of the deep-seated infection location caused by the gram positive and gram  negative  bacteries  could  be  done  with  nuclear  technique  using 99mTc-ciprofloxacin  radiopharmaceutical.   In  order  to  fulfill  the  necessity  of  this radiopharmaceutical,  the  development  of  formulation in  single  vial  based  on Sn(II)  chloride  and  tartaric  acid  instead  of  Sn(II) tartrat  has  been  carried  out. The  aim  of  this  investigation  is  to  obtained  the  optimum  condition of 99mTc-ciprofloxacin  preparation  with  maximum  labelling efficiency. Several  parameters  influencing  the  labelling  process  of 99mTc-ciprofloxacin such  as  the  amount  of  tartaric  acid,  pH  of  the  reaction,  the  amount  of  Sn(II) ion  as  a  reducing  agent  and  the  incubation  time  has been  studied.   The labelling  efficiency  and  the  radiochemical  purity  of 99mTc-ciprofloxacin  were determined  by  double  chromatography  system  using  Whatman  I/methyl ethyl  keton  to  determine  the  free 99mTc-pertechnetate  and  ITLCSG/(ethanol:water:ammonia = 2:5:1) to separate  the free 99mTc-reduced. The  optimum  preparation  condition  was  obtained  at  pH  =  2.95-3.20,  2  mg  of ciprofloxacin,  0.06  µg  of  tartaric  acid,  50  µg  of  SnCl22H2O  and  15  minutes incubation  time  at  room  temperature,  gave  90-93  %  of  labelling  efficiency,  in wchich was stable for 20 minutes at room temperature. Beside that, studies on the  effect  of  Na99mTcO4  solution  volume  to  the 99mTc-ciprofloxacin   labelling efficiency  was  carried  out.   Labelling with up to 0.3 mL of Na99mTcO4 solution volume gave less than 90 % labelling efficiency.Key words: radiopharmaceutical, ciprofloxacin, 99mTc, single vial